PENGUNAAN MEDIA PLATFROM TIKTOK DALAM MENINGKATKAN KEMAMPUAN MENYIMAK CERITA RAKYAT PADA SISWA KELAS VIII SMP MUHAMMADDIYAH 5 TIDORE - Burhanuddin Jamal; Masria Atib; Sartika Samad (Jurnal Pendidikan dan Ekonomi (JUPEK), 2026)
This study aims to improve the listening skills of folk tales through the use of TikTok platform media in eighth-grade students of Muhammadiyah 5 Tidore Junior High School. The background of this study is the low listening skills of students as indicated by the percentage of learning completion of only 19.2%. This is caused by the learning process that tends to be monotonous and the lack of use of varied learning media. This study is a Classroom Action Research (CAR) with the Kurt Lewin model which includes four stages, namely planning, implementation, observation, and reflection. The subjects of the study were 26 eighth-grade students consisting of 15 male students and 11 female students. Data collection techniques used observation, interviews, documentation, and other assessments. The results of the study indicate that the use of TikTok platform media can improve students' listening activities and abilities. In the first cycle, student learning activities reached 80%, then increased in the second cycle to 89.58%. This increase indicates that the use of TikTok media is effective in improving students' listening skills, so that indicators of learning success can be achieved.